(untitled) (REMUNOM, 2024)
Gestational Syphilis is a notifiable disease in Brazil, caused by the bacterium Treponema pallidum. Vertical transmission of the pathogen, when Treponema passes through the placenta, in untreated or inadequately treated pregnant women, is one of the main risks of the disease. Infection of the fetus causes high intrauterine morbidity and mortality. This study is an epidemiological profile of patients diagnosed with gestational syphilis in Brazil. This is a documentary study and data collection is through DATASUS/Tabnet.